New species and records of the genus Laena Dejean (Coleoptera: Tenebrionidae: Lagriinae) from the Malay Peninsula - Schawaller, Wolfgang; Bellersheim, Aron (Zootaxa, 2024)
From the Malay Peninsula (West Malaysia) 18 species of the genus Laena Dejean, 1821 are known so far. Additional two species are described herein as new: L. johoria sp. nov. and L. ledangica sp. nov. They originate exclusively from the southernmost, hitherto less explored Malaysian Federal State of Johor. Some new records of known Malaysian species are also listed.